The 10-Word Auditory Verbal Learning Test and Vocabulary Performance in 4- and 5-Year-Old Children. - Kasperek, Ann; Kingma, Annet; de Aguiar, Vânia (Journal of Speech, Language & Hearing Research, 2023)
Background: Understanding the different factors that determine vocabulary development in young children is essential for the diagnosis and rehabilitation of language disorders in children. Language development is closely related to other cognitive processes such as auditory verbal learning and memory. This research focuses on the development of a novel auditory verbal learning test (AVLT) for 4- and 5-year-old children within the Dutch population. This new test is an adaptation of the common AVLT for both older children and adults, usually including a list of 15 words. Considering the lower attention span and limited executive functioning in young children, the word list of this new instrument is reduced to 10 words. Besides, a second recognition form has been developed to improve the ability to distinguish between possible underlying learning and memory deficits. Method: Ninety-five preschool children (ages 4;0–5;12 [years;months]) were tested with this new AVLT 10-word test for kids (10WT-K), yielding different measures of verbal auditory memory. Forty-eight of 95 children received a recognition task with semantically unrelated items, and 47 of 95 received a recognition task with semantically related items. Three additional language skills were assessed to establish test validation: receptive and expressive vocabulary performance and nonword repetition. Outcome of the 10WT-K was related to scores on the language measures. Results: Positive correlations were found between the total score of the 10WT-K and all three aforementioned language skills. We found no correlations between frequency of error types (intrusions and repetitions) and language measures. Furthermore, children who were administered the recognition list with semantically related items showed fewer correct answers and more false-positive and falsenegative responses than children who received a recognition list with semantically unrelated items. Conclusions: The 10WT-K for young children can be used to (a) measure different aspects of auditory verbal learning and memory, (b) clarify the nature of possible verbal learning difficulties, and (c) identify a possible nature of language disorders. The word recognition task tested with semantically related items provides a more accurate measurement of individual differences, namely, in distinguishing retrieval and storage abilities. The significant relation found between auditory verbal short-term memory capacity and vocabulary performance in preschool children is a first step toward establishing test validity.